Fluorescent macrocycle-dye-anchor conjugates for sensing phospholipids in biomembranes - Oshchepkov, Alexander S.; Cruz Da Silva, Elisabete; Morozov, Boris; Aparin, Ilya O.; Kataev, Evgeny; Klymchenko, Andrey S. (Sensors and Actuators B-Chemical, 2023)
Negatively charged phospholipids can serve as biomarkers for a number of biological processes allowing detection of apoptosis in animal cells, drug-induced phospholipidosis as well as detection of bacteria. Selective detection of phospholipids thus represents an important but challenging goal. The development of fluorescent probes capable of selective recognition of specific phospholipids can be a promising solution to the problem. Along this line, we have developed the macrocycle-dye-anchor conjugates, in which the macrocycle recognizes the phosphate residue, hydrocarbon anchors ensure hydrophobic interaction with the membrane, and environment-sensitive fluorescent dye functions as a reporter unit. To the best of our knowledge, this is the first report of synthetic fluorescent probes for specific phospholipids using the macrocycle-dye-anchor concept. We have studied the effect of the structure of the anchor and the macrocycle on the resulting fluorescent response in the presence of two types of lipid vesicles: phosphatidylcholine as a model of healthy cells and phosphatidylcholine and phosphatidylserine (1:1), mimicking apoptotic cells. The properties of the obtained compounds were analyzed in various model media and in HeLa cells. The response of fluorescent probes has been found to be strongly dependent on the macrocycle structure, length of the anchor, nature of the buffer, and pH. The probes showed significant fluorescence enhancement in apoptotic cells, thus providing the proof of concept for the macrocycle-dye-anchor design.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Anion recognition; Anion sensing; Fluorescence imaging; Membrane probes; Naphthalimide; Phospholipids